2016
DOI: 10.3389/fpsyg.2016.00885
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Loyalty Related to Labor Inclusion of People with Disabilities

Abstract: Purpose: the purpose of this paper is to show that reporting the corporate commitment to labor exclusion of people with disability correlates with the increase of consumer loyalty.Methodology: It is a theoretical revision that will relate consumer loyalty to three main topics: disability and labor exclusion, responsible consumerism toward disability, and corporate communication to increase loyalty of those consumers that are concerned about this problem.Findings:     • Disability is an invisible phenomenon tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Conceptual framework and hypotheses development Studies are limited which examine consumer's attitudes toward hiring PwDs. However, a national study in the USA found that 92 per cent of the consumers felt more positive toward companies that employed them because it was assumed that these firms would care about their employees (González and Fernández, 2016).…”
Section: Impact Of Disabilitymentioning
confidence: 99%
“…Conceptual framework and hypotheses development Studies are limited which examine consumer's attitudes toward hiring PwDs. However, a national study in the USA found that 92 per cent of the consumers felt more positive toward companies that employed them because it was assumed that these firms would care about their employees (González and Fernández, 2016).…”
Section: Impact Of Disabilitymentioning
confidence: 99%
“…In accordance with the described scenario, in which customers are demanding that businesses act in a socially responsible manner ( Vrontis and Thrassou, 2007 ), it is of no surprise that managers are beginning to think of new customer-focused strategies to engage with the modern customer today ( González and Fernández, 2016 ). One of these interesting strategies to appeal to the customer in the current social values-driven Marketing 3.0 era is the development of servant leadership in service units –work units which are in close contact with customers–.…”
Section: Introductionmentioning
confidence: 89%
“…The extent to which a product or service provides freedom of choice, independence as well as benevolence, social justice, equality and environmental responsibility is becoming more and more crucial for customers when making purchase choices ( Martínez-Cañas et al, 2016 ), especially in a developed world, where consumption appears to have become an end in itself, through which customers find a voice to promote a better society ( Vrontis and Thrassou, 2007 ). Furthermore, customers are increasingly showing concerns about the effects of their purchase choices not only for themselves, but also for broader society ( Harrison, 2005 ; González and Fernández, 2016 ), which represents a strong embracement of transcendent motives in their actions. In other words, in addition to making purchase decisions with an eye on external benefits gained (i.e., extrinsic motivation) or the pleasure acquired from the purchase decision itself (i.e., intrinsic motivation), customers are more and more concerned about whether their purchase decisions contribute to solving the problems of someone else (i.e., transcendent motives).…”
Section: Introductionmentioning
confidence: 99%
“…The firm's emphasis is usually on social and cause‐related marketing activities to support PWDs (Min‐Young, Fairhurst, & Wesley, ; Peloza & Shang, ; Vauclair & Fischer, ) as critical for the firm's social acceptability (Klarsfeld, Ng, & Tatli, ). But such actions from “benevolent companies” are deemed to be insufficient as they keep PWDs at a distance and limit the possibility of integrating them into the value chain of an enterprise (González & Fernández, ).…”
Section: Diversity and Pwd Employabilitymentioning
confidence: 99%